FREE RADICAL SCAVENGING ACTIVITY OF BARK OF TERMINALIA BELLIRICA - C.MARY SHOBA DAS; S.GAYATHRI DEVI (International Journal of Pharma and Bio Sciences, 2015)
Terminalia bellirica Roxb belongs to the family Combretaceae, is distributed throughout the deciduous forests of India. The petroleum ether, chloroform, ethanol and aqueous extracts of the bark of Terminalia bellirica were screened for free radical scavenging activity against DPPH, ABTS, superoxide, nitric oxide, hydroxyl and hydrogen peroxide radicals. The scavenging activity was found to be dose dependent. The ethanol extract exhibits maximum scavenging activity while compared to other extracts. From the present study, it can be concluded that the bark of Terminalia bellirica possess good inhibitory activity. Hence it can be used as an easily accessible source of natural antioxidants.